2003
DOI: 10.1677/joe.0.1760001
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of calcium disposal from osteoclastic resorption hemivacuole

Abstract: One of the most remarkable but neglected aspects of osteoclast function is its unique adaptation that allows the cell to function despite its resorbing surface being exposed to extremely high levels of ambient Ca 2+. Recently our studies have provided evidence of continuous transcellular Ca 2+ disposal, suggesting that osteoclasts are able to prevent Ca 2+ accumulation within the resorptive hemivacuole. It has also been shown that matrix protein degradation products that accumulate within the osteoclast resorp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 26 publications
0
11
0
Order By: Relevance
“…Since it is widely accepted that interstitial pH in bone is ∼7.1 [4], it is clear that one cannot extrapolate measurements carried out in the reabsorption lacunae to the bone interstitium. Furthermore, the Ca 2+ o released in this environment does not flood the osteoclasts, but it is reabsorbed by the osteoclasts via Ca 2+ channels and released out of the cell via the non-resorbing (basolateral) membrane, and also by non-specific bulk transport, via transcytosis [35]. Indeed, Berger and colleagues [9] have shown that, under steady-state conditions, a resorbing osteoclast releases no more than 2 mM Ca 2+ via the non-resorbing, basolateral membrane, a value which is fully compatible with the sensitivity range of activation for CaR and that we have shown to regulate directly many aspects of osteoblast function through this receptor.…”
Section: Car In Bonementioning
confidence: 99%
“…Since it is widely accepted that interstitial pH in bone is ∼7.1 [4], it is clear that one cannot extrapolate measurements carried out in the reabsorption lacunae to the bone interstitium. Furthermore, the Ca 2+ o released in this environment does not flood the osteoclasts, but it is reabsorbed by the osteoclasts via Ca 2+ channels and released out of the cell via the non-resorbing (basolateral) membrane, and also by non-specific bulk transport, via transcytosis [35]. Indeed, Berger and colleagues [9] have shown that, under steady-state conditions, a resorbing osteoclast releases no more than 2 mM Ca 2+ via the non-resorbing, basolateral membrane, a value which is fully compatible with the sensitivity range of activation for CaR and that we have shown to regulate directly many aspects of osteoblast function through this receptor.…”
Section: Car In Bonementioning
confidence: 99%
“…Vesicular transcytosis is important in bone-resorbing osteoclasts. In contrast, during bone resorption, a large amount of Ca 2ϩ (up to 40 mM) and P i ion is generated within the osteoclast hemivacuole (10). The precise mechanisms involved in the disposal of Ca 2ϩ and P i are not clear.…”
mentioning
confidence: 99%
“…Guan et al [13] reported that when incubated with vascular smooth muscle cells, icariin blocked calcium channels that are either ligand- There are different viewpoints about the consequence of change in [Ca 2+ ] i in osteoclasts. Calcitonin, IL-4 and protein tyrosine kinase (PTK) inhibitors suppress osteoclast activity via acutely increasing the [Ca 2+ ] i , suggesting that elevation of [Ca 2+ ] i plays an inhibitory role in osteoclast function [14] . However, Berger et al [15] argue that an increase in [Ca 2+ ] i may be associated with activation, inhibition, or may have no effect on bone resorption.…”
Section: Discussionmentioning
confidence: 99%